Disseminated Rhodococcus equi infection in a patient with Hodgkin lymphoma - Mikić, Dragan; Djordjević, Zoran; Sekulović, Leposava; Kojić, Miroslav; Tomanović, Branka (Vojnosanitetski pregled, 2014)
Introduction. Rhodococcus (R) equi is an opportunistic, uncommon human pathogen that causes mainly infection in immunocompromised hosts. The disease is usually presented as subacute pneumonia that is mostly cavitary and sometimes bacteremic. Case report. We reported the extremly rare case of a 43-year-old woman with Hodgkin lymphoma, who developed R. equi pulmonary infection after recieving multiple courses of chemotherapy. Secondary, the patient developed bacteremia, leading to sepsis and dissemination of R. equi infection in many extrapulmonary sites. At addmission the patient was febrile, tachypnoic, tachycardic, hypotensive, with facial edema, splenomegaly, positive meningeal signs, left hemiparesis and paraparesis. Laboratory data included erythrocyte sedimentation rate (ESR) > 140 mm/h, C-reactive protein (CRP) 143.0 mg/L, red blood cells (RBC) 2.14 × 1012/L, whyite blood cells (WBC) 2.8 × 109/L, lactate dehydrogenase (LDH) 706 U/L, serum albumin 26 g/L, sodium 127 mmol/L and potassium 2.7 mmol/L. Blood culture and culture of sputum and empyema were positive for R. equi. Imaging studies demonstrated a large right cavitary pneumonia and abscess, empyema, pericarditis, mediastinal and intra-abdominal lymphadenopathy, brain and psoas abscesses, osteomyelitis and spondylodiscitis. The patient recovered completely after a 12-month treatment with combinations of parenteral and oral antibiotics (meropenem, vancomycin, teicoplanin, ciprofloxacin, rifampicin, macrolides etc), including drainage of abscesses and empyema. Eight years after completition of the treatment the patient was without recurrence of R. equi infection and lymphoma. Conclusion. Since the eradication od R. equi is very difficult, it is very important to make the diagnosis and initiate appropriate antibiotic therapy as soon as possible.
Keywords: rhodococcus equi; hodgkin disease; immunologic deficiency syndromes; infection; sepsis; anti-bacterial agents; drug therapy; combination